2000
DOI: 10.1177/00034894001090s502
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Bone Studies of the Human Peripheral Vestibular System

Abstract: Quantitative studies of the vestibular system with serially sectioned human temporal bones have been limited because of difficulty in distinguishing hair cells from supporting cells and type I from type II hair cells. In addition, there is only a limited amount of normative data available regarding vestibular hair cell counts in humans. In this study, archival temporal bone sections were examined by Nomarski (differential interference contrast) microscopy, which permitted visualization of the cuticular plate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(112 citation statements)
references
References 13 publications
(17 reference statements)
9
93
1
2
Order By: Relevance
“…The mean type I:II HC ratios of 2.3 (SD 0.8) and 1.1 (SD 0.4) in the crista and macula, respectively, estimated in this study are in range of ratios of approximately 1.6-2.4 in the central zone of the crista (Rauch et al 2001;Lopez et al 2005) and 1.4-1.7 in the otolith end organ macula (Gopen et al 2003;Merchant et al 2000) in humans. Methods employed in this study cannot consistently distinguish between the central and peripheral zones in the cristae or striolar and nonstriolar regions in the maculae.…”
Section: Effects Of Hair Cell Counting Techniquesupporting
confidence: 45%
“…The mean type I:II HC ratios of 2.3 (SD 0.8) and 1.1 (SD 0.4) in the crista and macula, respectively, estimated in this study are in range of ratios of approximately 1.6-2.4 in the central zone of the crista (Rauch et al 2001;Lopez et al 2005) and 1.4-1.7 in the otolith end organ macula (Gopen et al 2003;Merchant et al 2000) in humans. Methods employed in this study cannot consistently distinguish between the central and peripheral zones in the cristae or striolar and nonstriolar regions in the maculae.…”
Section: Effects Of Hair Cell Counting Techniquesupporting
confidence: 45%
“…He reported a decrease in the number of vestibular hair cells after the age of 20 years old and a decrease in the number of vestibular ganglion neurons after the age of 50 years. On the other hand, Merchant et al (2000) reported a gradual loss in the number of vestibular hair cells in all endrogans, with relative sparing of the utricle, with increasing age [62]. These early reports, which estimated the number of vestibular hair cells and neurons from serial sections of the temporal bones, may have been biased as they were based on several assumptions such as the spherical shape and uniform size of the hair cells as well as the constant shrinkage and thickness of the specimen.…”
Section: Cellular Changes In Aging Of the Vestibular Systemmentioning
confidence: 99%
“…Gopen et al (2003) used the same method to estimate the number of hair cells in the utricle but they failed to show an agedependent decrease in the number of hair cells [64]. It remains unclear whether this result reflects the relative sparing of the utricle in age-related loss of hair cells [62], or is due to bias caused by the paucity of the number of temporal bones examined. In contrast to numerous reports regarding animal models of age-related hearing loss, animal models of agerelated vestibular dysfunction have rarely been reported.…”
Section: Cellular Changes In Aging Of the Vestibular Systemmentioning
confidence: 99%
“…In contrast, hair cell numbers in the balance organs of humans appear to reach steady levels after 14 weeks of gestation (Rosenhall 1972(Rosenhall , 1973Merchant et al 2000). Rodents are often imperfect models for human conditions, but continuing investigations in neonatal and more mature mice hold the potential to reveal just how maturational changes in mammals restrict molecular circuitry and regenerative processes that are so effective in allowing recovery of balance and hearing after damage in non-mammals.…”
Section: Implications For Regenerationmentioning
confidence: 99%